2020
DOI: 10.1590/0001-3765202020181391
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and phenology of epigeal Coleoptera assemblages in lettuce and tomato crops in Northern Buenos Aires province, Argentina

Abstract: Epigeic coleopteran species are linked by complex trophic webs and implicated in several ecosystem services for agriculture. Although there are reports of grounddwelling Coleopterans inhabiting main extensive agroecosystems, their assemblages in horticultural crops in Argentina have been little explored. We examined the community structure of epigeal Coleoptera assemblages of Curculionidae, Carabidae, Staphylinidae and Coccinellidae species, in lettuce and tomato crops located in Northern Buenos Aires province… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…According to previous studies [6,[70][71][72][73], our results showed that coleopteran communities are highly correlated with plant communities. Conventional orchards were very similar in their composition of plants and beetles, again illustrating how the constraining nature of management practices leads to more homogeneous communities [24,54,74]. Organic orchards, however, showed a more heterogeneous composition; moreover, orchards located on the same hillside aspect seemed to harbor slightly more similar plant and beetle communities.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…According to previous studies [6,[70][71][72][73], our results showed that coleopteran communities are highly correlated with plant communities. Conventional orchards were very similar in their composition of plants and beetles, again illustrating how the constraining nature of management practices leads to more homogeneous communities [24,54,74]. Organic orchards, however, showed a more heterogeneous composition; moreover, orchards located on the same hillside aspect seemed to harbor slightly more similar plant and beetle communities.…”
Section: Discussionmentioning
confidence: 90%
“…These species have a natural tolerance for some herbicides or exhibit traits that allow them to withstand the negative effects of this treatment [74]. In our examination of coleopterans, families that exploit widely distributed resources, such as Coccinellidae or Curculionidae, contributed more to the structure of conventional orchards, reflecting how more generalist beetles are less constrained by management practices such as weed and pest control [24,77].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations